Semiotic function of toponyms in "Tales of Peculiar" by Ransom Riggs - Chikarkova, Mariya (My University, 2022)
The research presents one of the important components of the artistic world "Tales of the Peculiar" by R. Riggs - toponyms. Toponyms of different classes (choronyms, insulonyms, oceanonyms, etc.) are present in every fairy tale, but their functions and types differ. Thus, real toponyms (America, Madagascar, Ceylon, etc.) perform primarily a nominative function and are usually iconic signs. This allows the author to create the illusion of pseudo-documentary which is a characteristic feature of postmodern aesthetics and style of Ransom Riggs. Quasi-toponyms are used by the writer as signs-symbols, their conventionality becomes clear only within the sign system of the whole collection. They are expressive and often have a negative evaluative connotation (Swampmuck, Little Disappointment, etc.). In two fairy tales ("Cocobolo" and "The Pigeons of Saint Paul's") toponyms gain a dominant position, having become part of the names. They act here not just as signs-symbols, but perform a plot-forming function and form the basis of the ontology of the writer's artistic world. Decoding of toponyms by means of literary onomastics and semiotics allows understanding better the author's concept of reality and features of the writer's idiosyncrasy.
Keywords: literary onomastics; semiotics; toponyms; symbol; pseudo-documentary; Ransom Riggs